Deadline-Aware Redundant Transmission on Multi-Paths for Real-Time Service - Hyeonwoo Kang; Seungwoo Hong; Donghyun Kang; Donghyeok An (IEEE Access)
This study addresses the challenge of meeting deadlines in real-time applications such as video streaming and online gaming, in which data block delivery is time sensitive. Traditional loss-recovery solutions such as retransmission are inadequate, particularly in multi-path networks with long round-trip times, resulting in delays and missed deadlines. The proposed deadline-aware redundant transmission (DART) approach proactively transmits redundant packets across multiple paths, considering the next transmission time and one-way delay on each path to meet deadlines with minimal overhead. It also addresses deadlocks caused by insufficient network capacity by prioritizing the transmission of the smallest data block in the queue. DART, which operates independently of existing schedulers, simplifies implementation and reduces disturbances to existing schedulers. Simulation results demonstrate that DART increases the block transmission success rates by 5% to 10%, depending on the network conditions, while requiring minimal overheads.